The influence of the personal characters on the leadership administrative behaviors in the Ministry of Education in The Sultanate of Oman. This is via its impact on the transformational leadership as a changeable influence - Albuloshi, Mohammed Suleiman Kamis (Journal of Educational and Psychological Sciences, 2022)
This study aims to study the influence of the personal characters on the leadership administrative behaviors in the Ministry of Education in The Sultanate of Oman. This is via its impact on the transformational leadership as a changeable influence. This research based on the analytical description style and the researcher uses the survey as a tool to collect data for the study. He also analyses the survey with (Structural Equation Model) through the use of PLS Program and he has used the Stats Package (SPSS). This survey was conducted on the study community consists of 375 members. The community was divided into 3 main jobs categories which are Deputy school principle, Head of The Department and officer, between males and females. It was held on the Directorates Departments of the Ministry of Education. The results have shown the direct effect of the personal characters on the leadership behavior with the medium effect degree (0.657) on the (Cohen Standers, 1988). This is going to develop the performance of the job and the stuff. It shows also that there is a direct positive influence for the patterns of transformational leadership on a leader character with a high degree according to the (Kohine Scale) which is (0.875). Moreover, the researcher recommended the importance of the development of the personal behaviors of the leaders via the use of transformational leadership style as an educational methodology in the leaders preparation programs.
Keywords: personal characters; transformational leadership; administrative leaders